2019
DOI: 10.1108/sef-07-2019-0270
|View full text |Cite
|
Sign up to set email alerts
|

Financial technology: a review of extant literature

Abstract: Purpose This paper aims to undertake a thematic review of academic papers on financial technology (FinTech) to identify three broad categories for the purpose of classifying extant literature. The paper summarizes the research and findings in this emerging field. Thereafter, it identifies the gaps and provides directions for further research. Simultaneously, the paper collates technical terms related to FinTech that appear repeatedly in each category and explains them. Finally, the study highlights the lessons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(65 citation statements)
references
References 106 publications
0
46
0
5
Order By: Relevance
“…Stewart and Jurjens (2018) identified that data security strongly impacts the intention to use FinTech. In contrast, Sangwan et al (2019) reported that perceived security has no direct relationship on intention to use. Accordingly, it is proposed that: H3: Cyber-security risks has a significant relationship on behavioural intention to use FinTech services.…”
Section: Cyber-security Risksmentioning
confidence: 89%
See 3 more Smart Citations
“…Stewart and Jurjens (2018) identified that data security strongly impacts the intention to use FinTech. In contrast, Sangwan et al (2019) reported that perceived security has no direct relationship on intention to use. Accordingly, it is proposed that: H3: Cyber-security risks has a significant relationship on behavioural intention to use FinTech services.…”
Section: Cyber-security Risksmentioning
confidence: 89%
“…In the FinTech area, the introduction of new FinTech technologies could involve unforeseen cybersecurity risk which caused by untrusted and anonymous data users (Sangwan et al, 2019). Security risk is "the potential loss due to fraud or a hacking that compromises the security of the financial transactions of FinTech" (Ryu, 2018, p. 548).…”
Section: Cyber-security Risksmentioning
confidence: 99%
See 2 more Smart Citations
“…The fast and rapid development in Fintech can be equally disruptive if it is not regulated properly (Vijayanti, 2017). As the FinTech is in its early stage of development and the impact of FinTech on various stakeholders can only be understood by using the dimensions such as regulation (Sangwan, 2019).…”
Section: Islamic Fintech and Regulatory Challengesmentioning
confidence: 99%